Propofol protects cardiomyocytes from doxorubicin-induced toxic injury by activating the nuclear factor erythroid 2-related factor 2/glutathione peroxidase 4 signaling pathways. Issue 4 (1st April 2022) - Lu, Ziyun; Liu, Zhiyi; Fang, Bei
ABSTRACT: Propofol offers important protective effects in ischemia/reperfusion-induced cardiomyocyte injury, but its specific mechanisms in doxorubicin (DOX)-induced cardiotoxicity have not been investigated. In this paper, we attempted to explore the effects of propofol on DOX-induced human cardiomyocyte injury and its related mechanisms. H9c2 cell viability was assessed by cell counting kit-8 and lactate dehydrogenase assay kit. Nuclear factor erythroid 2-related factor 2 (NRF2)/glutathione peroxidase 4 (GPx4) signaling pathway-related protein levels were measured by Western blot. Ferroptosis was evaluated by corresponding kits and Western blot and apoptosis was detected by CCK-8, terminal deoxynucleotidyl transferase dUTP nick-end labeling and Western blot. Oxidative stress was assessed by reactive oxygen species kit and the commercial kits, and inflammation response was analyzed by enzyme-linked immunosorbent assay and Western blot. The results showed that propofol attenuated DOX-induced cytotoxicity and activated Nrf2/GPx4 signaling pathways in H9c2 cells. In addition, propofol also alleviated DOX-induced ferroptosis, increased cell viability and inhibited apoptosis, oxidative stress and inflammatory responses in H9c2 cells through activation of Nrf2/GPx4 signaling pathways. In summary, propofol provides the protection against DOX-induced cardiomyocyte injury by activating Nrf2/GPx4 signaling, providing a new approach and theoretical basis for the repair of cardiomyocytes. Graphical abstract: uf0001